Optical properties and applications of SnS2 SAs with different thickness - Mengli Liu (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
Q-switched lasers have occupied important roles in industrial applications such as laser marking, engraving, welding, and cutting due to their advantages in high pulse energy. Here, SnS2-based Q-switched lasers are implemented. Considering that SnS2 inherits the thickness sensitive optical characteristics of TMD, three kinds of SnS2 with different thickness are characterized in terms of nonlinearity and used to realize the Q-switched pulses under consistent implementation conditions for comparison tests. According to the results, the influence of thickness variation on the nonlinear performance of saturable absorber, such as modulation depth and absorption intensity, and the influence on the corresponding laser are analyzed. In addition, compared with other traditional saturable absorbers, the advantage of SnS2 in realizing ultrashort pulses is also noticed. Our work explores the thickness-dependent nonlinear optical properties of SnS2, and the rules found is of great reference value for the establishment of target lasers.